When Love Leaves Scars: A Portrait of Toxic Relationships in a Phenomenological Study - Fanny Fadesti, Pralayar; Graciela Pirade, Agatha; Satriana, Satriana; Sasmita Trisofika, Risma (Psikostudia : Jurnal Psikologi, 2025)
Toxic relationship is a phenomenon of unhealthy relationships commonly experienced by Generation Z, characterized by excessive control, manipulation, verbal and physical abuse, and emotional dependency that undermines individual autonomy and mental health. This study aims to describe the emergence of toxic relationships, the dynamics of emotional dependency, relational patterns, exit barriers, as well as the impacts and post-traumatic growth. The method used is qualitative research with a phenomenological approach. Three participants aged 20 were selected through snowball sampling. Data was collected through non-participant observation and structured interviews, then analyzed using thematic analysis according to Braun & Clarke (2006) with triangulation to ensure credibility. The results indicate that toxic relationships arise due to changes in partner behavior, the loss of a supportive figure, and inconsistent commitment. Exit barriers emerge due to feelings of love, sacrifice, and manipulation. After breaking up, individuals experience trauma but also grow in the form of increased self-awareness and the ability to establish boundaries. This study emphasizes the importance of psychoeducation and institutional support.Hubungan toksik merupakan fenomena hubungan yang tidak sehat yang sering dialami oleh Generasi Z, ditandai dengan kontrol berlebihan, manipulasi, kekerasan verbal dan fisik, serta ketergantungan emosional yang merusak otonomi dan kesehatan mental individu. Penelitian ini bertujuan untuk menggambarkan munculnya hubungan toksik, dinamika ketergantungan emosional, pola hubungan, hambatan untuk keluar, serta dampak dan pertumbuhan pasca-trauma. Metode yang digunakan adalah penelitian kualitatif dengan pendekatan fenomenologis. Tiga peserta berusia 20 tahun dipilih melalui teknik sampling bola salju. Data dikumpulkan melalui observasi non-partisipan dan wawancara terstruktur, kemudian dianalisis menggunakan analisis tematik sesuai dengan Braun & Clarke (2006) dengan triangulasi untuk menjamin kredibilitas. Hasil penelitian menunjukkan bahwa hubungan toksik muncul akibat perubahan perilaku pasangan, hilangnya figur pendukung, dan ketidakkonsistenan dalam komitmen. Hambatan untuk keluar muncul akibat perasaan kasih sayang, pengorbanan, dan manipulasi. Setelah perpisahan, individu mengalami trauma tetapi juga tumbuh dalam bentuk peningkatan kesadaran diri dan kemampuan untuk membangun batas. Penelitian ini menekankan pentingnya pendidikan psikologis dan dukungan institusional.